Kadar Protein Terlarut dalam Albumin Ikan Gabus (Channa striata dan Channa micropeltes) Asal Bogor SOLUBLE ROTEIN CONCENTRATION IN SNAKEHEAD FISH ALBUMIN BOGOR ORIGIN (CHANNA STRIATA AND CHANNA MICROPELTES) - Alviodinasyari, Rizky; Pribadi, Eko Sugeng; Soejoedono, Retno Damayanti (Jurnal Veteriner, 2019)
Snakehead fish is currently used by the public as a health treatment because it has a higher content of albumin protein than others. The Research aimed was determined the protein quality and comparison levels in two species of snakehead fish, Channa striata and Channa micropeltes, derived from Bogor Regency. Protein concentration level of C. micropeltes and C. striata after drying for five minutes as much as 0.830 mg/mL and 0.803 mg/mL and these concentration were higher than dried for 10 and 15 minutes. Protein concentration levels of the two species were not significantly different. The molecular weight of albumin protein from both species were 65.56 kDa to dried for five minutes, 65.08 kDa to dried for 10 minutes, and 64.91 kDa to dried for 15 minutes. The Results concluded that there were no differences in protein levels in the fish meat and skin of the two species. Drying treatment affects the molecular weight of snakehead fish albumin protein.